MALNUTRITION AT HOSPITAL ADMISSION AND ITS ASSOCIATED FACTORS IN INTERNAL MEDICINE INPATIENTS - Wita Rizki Amelia; Astrine Permata Leoni; Ahmad Syauqy; Purwita Wijaya Laksmi; Martalena Br Purba; Etika Ratna Noer; Lora Sri Nofi; Befi Sundari; Mita Arini (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2023)
ABSTRACTBackground: Malnutrition at hospital admission may adversely affect patients' clinical outcomes. The Global Leadership Initiative on Malnutrition (GLIM) recently set a standard of measurable criteria to diagnose malnutrition. Objectives: This study aimed to determine the proportion and risk factors of malnutrition at hospital admission.Materials and Methods: A cross-sectional observational study was conducted in the internal medicine ward of the National General Central Hospital, Dr. Cipto Mangunkusmo (RSCM), Jakarta, from January to May 2022. Subjects aged 18 and above were recruited for this study. Malnutrition at hospital admission was defined according to the GLIM criteria. Then, the data were analyzed using multiple logistic regression to determine malnutrition risk factors, presented by odds ratios (OR) and 95% confidence intervals (CI).Results: A total of 231 subjects were enrolled in the study. Among them, 85.3% were malnourished according to the GLIM criteria. In addition, subjects with a severe to total dependency on functional status (OR 9.406, 95%CI: 3.147–28.109), inadequate energy intake (OR 2.718, 95%CI: 1.197–6.172), and multimorbidity (OR 2.337, 95%CI: 1.045–5.228), were significantly associated with malnutrition at hospital admission cases. Conclusion: According to the GLIM criteria, the proportion of malnutrition at hospital admission is high. The risk factors of malnutrition at hospital admission include low functional status, inadequate energy intake, and multimorbidity.Keywords : Malnutrition; Nutritional status; Nutrition assessment; Hospital admission; Internal medicine, Inpatients